Archiduino as a Media for Learning Physics: A Laboratory Study - Akhdinirwanto, R. Wakhid; Diana, Abi; Hakim, Yusro Al; Kurniawan, Eko Setyadi (JIPF (Jurnal Ilmu Pendidikan Fisika), 2025)
Physics concepts and quantities in Physics subjects at school can be presented realistically through a series of practical activities and demonstrations using learning aids. An Arduino-based Archimedes' law teaching aid (Archiduino) has been designed as a physics learning medium. The research method adapts the ADDIE model which consists of Analyze, Design, Development, Implementation and Evaluation. In order to determine the suitability of the teaching aids, equipment trials and product validation have been carried out by physics material experts and media experts. Based on the research results, it was obtained: (1) The Arduino-based Archimedes' Law teaching aid which was designed to meet the valid criteria based on the results of the assessment by media experts obtained an average percentage of 88.31% in the valid category and the results of the assessment by material experts obtained an average percentage of 87.96%. in the valid category. (2) The Arduino-based Archimedes' Law teaching aid met the practical criteria in a limited trial of 10 students, and received student responses to the teaching aid in the aspects of benefits, presentation of the tool and physical appearance with an average percentage of 86.86% in the very good category. Thus, the Arduino-based Archimedes' Law teaching aid is valid and practical so it can be used as an alternative teaching aid in physics learning.